ANALISIS PENGARUH BERBAGI PENGETAHUAN DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KAPABILITAS INOVASI DAN KINERJA PERUSAHAAN PADA SEKTOR INDUSTRI KREATIF - , Fadlik Febrian, Dr. Amin Wibowo, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Innovation is an important factor in an industry, especially to improve firm performance. The increasingly tougher competition is driving companies to improve their innovation and performance. Based on the diffusion of innovation theory, one of the factors that can increase firm innovation capability is the practice of knowledge sharing because it can be generate ideas or new insight needed to innovate. However, the innovation process also requires the right actions and decisions for it to success. Aspects of the entrepreneurial orientation that is based on the company's proactive attitude and courage in taking risky decisions is one determining factor that support the company success and capability to innovate. To prove the influence of knowledge-sharing and entrepreneurial orientation in improving companiesâ innovation and performance, the study was conducted on 200 craft industries in D.I. Yogyakarta (Yogyakarta Special Region). This study developed a theoretical model with five hypotheses proposed to be tested using a structural equation modeling (SEM) analysis technique. The results demonstrated that entrepreneurial orientation has a positive impact on the companiesâ innovation capability and performance. Knowledge-sharing practices proved also to improve their innovation capability.